Pi Hole on SOE Computer Network using Raspberry Pi 3 Model B+ to Optimize Bandwidth Management and Improve Employee Performance - Rahmat Novrianda Dasmen; Darwin Darwin; Irham Irham; Bima Riansyah (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
State-Owned Enterprises (BUMN) are government agencies that currently have computer networks and are supported by internet services, which are always used in the work process of BUMN employees. Along with the development of the Internet of Things (IoT) devices, good internet service is very much needed by BUMN as it will affect the performance of BUMN employees. However, the problem that often occurs in internet services in BUMN is slow internet speed, which hinders the work process of BUMN and decreases the performance of BUMN employees. It should be noted that good internet service depends on the bandwidth used, so it is very important to have good bandwidth management applied to the BUMN computer network. So far, BUMN have done several things related to bandwidth management, ranging from access restrictions, even distribution of bandwidth, and the implementation of an authentication system to connect to the BUMN internet network. However, some of these things are still not enough to guarantee no wasteful use of bandwidth, which occurs because when operating some work-supporting websites, various types of digital ads will automatically appear, consuming a significant amount of bandwidth. Therefore, in this Action Research study, a Pi Hole to control digital ads was implemented that can automatically appear and use large amounts of bandwidth. By using Raspberry Pi 3 Model B+, the development of Pi Hole will limit digital ads from appearing when accessing websites or other IoT devices used by BUMN so that bandwidth usage will be more optimal in BUMN work processes. This will also improve the performance of BUMN employees, where with maximum bandwidth, the work process of BUMN can be accelerated.